The knowledge, attitude, and practice regarding pap smear, cervical cancer, and human papillomavirus among women attending a mother and child health clinic in Kuantan, Malaysia - Tg. Abdul Rahman, Tg. Faten Nurjihan; A. Rahman, Nor Azlina; Mohd Shafri, Mohd Affendi; Haque, Mainul (Wolters Kluwer ‑ Medknow, 2019)
Background: Cervical cancer (CC) is a foremost reason of global cancer death in women, and a good portion remains with the developing countries. This study was conducted to assess the knowledge, attitude, and practice regarding Pap smear, CC, and Human Papillomavirus (HPV) among the women attending a Mother and Child Health Clinic in Kuantan, Malaysia. Materials and Methods: A total of 120 respondents involved in this cross‑sectional study. The convenience sampling was to select the respondents. The data were collected from in 2013. Results: The mean age 32.19 years. Up to 54.2% of respondents never had Pap smear in the past 5 years, while over 67.5% of respondents never had HPV vaccination. There was a significant correlation between knowledge with attitude (P < 0.001) and attitude with practice (P < 0.001) regarding Pap smear, CC, and HPV. However, knowledge and practice regarding Pap smear, CC, and HPV was not significantly correlated (P = 0.525). There was no significant correlation between mean age and knowledge (P = 0.455) while there was a significant correlation between mean age with attitude (P = 0.011) and practice (P < 0.001) regarding Pap smear, CC, and HPV. It was also shown that there were differences between races in term of knowledge and attitude (P < 0.05). However, there was no significant difference in term of practice regarding Pap smear, CC, and HPV (P > 0.05) between races. Conclusions: Important barriers to Pap smear screening among women are highlighted through this study. The health institution involved needs to come up with better strategies to deal with these barriers to improve the awareness of women regarding Pap smear, CC, and HPV.